Analysis of the model of interdependence of thermoelement branch geometry and reliability indicators of the single-stage cooler - Zaykov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2017)
The effect of the thermoelement branch geometry on the main reliability indicators of the single-stage thermoelectric cooling device for a variety of temperature gradients in the range of practical use of coolers in various operation modes has been considered. To achieve the assigned objective of bettering reliability indicators of thermoelectric coolers, a reliability-oriented model has been developed. The model relates the failure rate and the probability of failure-free operation with the geometry of thermoelement branches, energy indicators and operation conditions. The analysis was performed for a variety of temperature gradients, a fixed tempo load and various modes of operation. Analysis of the developed model has shown the possibility of improvement of the reliability indicators of the single-stage thermoelectric coolers by selection of the thermoelement branch geometry. Analytical relations between the failure rate and the geometry of thermoelements, energy indicators of the coolers have been established. It was shown that the choice of the thermoelement geometry can give more than a two-fold reduction in the failure rate. The developed model which can be used in computer-aided design enables development of single-stage thermoelectric coolers with consideration of restrictive requirements to size, weight, power consumption with a possibility of choice of a compromise design variant